The Development of Anthropomorphism in Interaction: Intersubjectivity, Imagination, and Theory of Mind - Airenti, Gabriella (Frontiers in Psychology, 2018)
Human beings frequently attribute anthropomorphic features, motivations and behaviors to animals, artifacts, and natural phenomena. Historically, many interpretations of this attitude have been provided within different disciplines. What most interpretations have in common is distinguishing children’s manifestations of this attitude, which are considered “natural”, from adults’ occurrences, which must be explained by resorting to particular circumstances. In this article, I argue that anthropomorphism is not grounded in specific belief systems but rather in interaction. In interaction, a nonhuman entity assumes a place that generally is attributed to a human interlocutor, which means that it is independent of the beliefs that people may have about the nature and features of the entities that are anthropomorphized. This perspective allows us to explain the problems that emerge if we consider anthropomorphism as a belief: (i) adults under certain circumstances may anthropomorphize entities even if they perfectly know that these entities have no mental life; (ii) according to the situation, the same entity may be anthropomorphized or treated as an object; (iii) there is no consistency among the entities that are anthropomorphized; (iv) there is individual variability in anthropomorphization, and this variability derives from affective states rather than from different degrees of knowledge about the entity that is anthropomorphized or greater or lesser naivety of the person who anthropomorphizes. From this perspective, anthropomorphism is a basic human attitude that begins in infants and persists throughout life. The difference between adults and children is not qualitative but rather a matter of complexity.